An ethnobotanical survey of spice, aromatic and medicinal plants used in La Molana, Atrato-Choco, Colombia: Basis for biodiversity conservation (2018)
A characterization and analysis of the production systems of aromatic, medicinal and spice plants (AMSP) was carried out in La Molana, Atrato-Chocó, Colombia throughout the identification of their biophysical, socioeconomic and financial characteristics, in order to propose agroecological alternatives that solve the problems and identified needs in said systems; applying methodologies and evaluation indicators of agricultural systems addressed to sustainable rural development, design, implementation and evaluation of agroforestry arrangements, agroforestry systems accompanied by WOST analysis, and agroforestry planning of productive units (APPU), this information was collected through the application of a focal workshop and semi-structured questionnaires to 40 farm producers. Therefore, eight productive units (UP) with four plots and four rooftop, which was characterized throughout a simple random sampling without replacement. The results indicate that these farm producers destine 15.6 ha to AMSP production, from which 11 ha are crops structured in plots within forests and 4.6 ha are destined to crops in roofs around the houses. The units produce on average, 110 units (bunches) per week, which are offered to informal vendors in the market place of Quibdo-Choco, Colombia with prices which ranged from COP $ 1000 to COP $ 3000 according to plant size and species. Likewise, was determined that the economic incomes of the AMSP units depend mainly on the following planted species: Cilantro (Coriandrum sativum L.), cimarron (Eryngium foetidum L.), Albahaca (Ocimum basilicum L.) and Oregano (Origanum vulgare L.), which are the most economically important species in the study area.